Pengaruh Kualitas Produk dan Inovasi Produk Terhadap Minat beli Produk Hadalabo - Ella Anastasya Sinambela; Yofina Bintang Cahyani (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2026)
Beauty products have been around for hundreds of years. Constantly changing beauty standards have kept the beauty industry evolving, boosting not only sales but also consumer purchasing interest. Products are the primary impression consumers make when considering a purchase. The purpose of this study was to determine the influence of product quality and innovation on beauty product purchase intention. This study used 77 respondents and employed multiple linear regression analysis. The results demonstrated that product quality and innovation influence purchase intention for beauty products.